Oxidative Stress Leads to β-Cell Dysfunction Through Loss of β-Cell Identity - Leenders, Floris; Groen, Nathalie; de Graaf, Natascha; Engelse, Marten A.; Rabelink, Ton J.; de Koning, Eelco J. P.; Carlotti, Françoise (Frontiers in Immunology, 2021)
Pancreatic β-cell failure is a critical event in the onset of both main types of diabetes mellitus but underlying mechanisms are not fully understood. β-cells have low anti-oxidant capacity, making them more susceptible to oxidative stress. In type 1 diabetes (T1D), reactive oxygen species (ROS) are associated with pro-inflammatory conditions at the onset of the disease. Here, we investigated the effects of hydrogen peroxide-induced oxidative stress on human β-cells. We show that primary human β-cell function is decreased. This reduced function is associated with an ER stress response and the shuttling of FOXO1 to the nucleus. Furthermore, oxidative stress leads to loss of β-cell maturity genes MAFA and PDX1, and to a concomitant increase in progenitor marker expression of SOX9 and HES1. Overall, we propose that oxidative stress-induced β-cell failure may result from partial dedifferentiation. Targeting antioxidant mechanisms may preserve functional β-cell mass in early stages of development of T1D.